Thrombosis and Haemostasis VTH Congress 1975
DOI: 10.1055/s-0039-1689328
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Studies on Artificial Surface/Protein/Platelet Interactions

Abstract: To highlight the mechanisms of artificial surface/protein/platelet interactions, results obtained by various methods have been integrated to elucidate some of the correlations between phenomena which occur at the macromolecular level and subsequently influence those at the cellular level, such as platelet adhesion. Microcinematographic evidence obtained under the controlled conditions of the Stagnation Point Flow Experiment (SPFE) indicate that, even on glass, platelet adhesion commences only after 30-60 sees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Nyilas et al [3,4] and Filisko et al [5] examined the adsorption of blood proteins onto various surfaces and obtained results suggesting that initially adsorbed protein undergoes more conformational change than does a subsequent layer. Using a semi-quantitative approach, Norde and Lyklema [6] resolved the integral adsorption heat into its components for the adsorption of albumin and ribonuclease onto polystyrene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nyilas et al [3,4] and Filisko et al [5] examined the adsorption of blood proteins onto various surfaces and obtained results suggesting that initially adsorbed protein undergoes more conformational change than does a subsequent layer. Using a semi-quantitative approach, Norde and Lyklema [6] resolved the integral adsorption heat into its components for the adsorption of albumin and ribonuclease onto polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…Koutsoukos et al [8] measured ads H for the adsorption of albumin on hematite under varying conditions of charge on the protein and the substrate, finding maximal evolution of heat near the isoelectric point of the protein. Several authors [3][4][5][6][7][8][9] have obtained exothermic heats upon adsorption of protein onto like-charged substrate, indicating that Coulomb forces do not necessarily dominate spontaneous adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we discuss the preparation, structure, and surface characteristics of A-B-A tri-block copolymers consisting of DL-isomers of poly(ymethyl glutamate) as the A component and polybutadiene as the B component. Conformation studies ofpoly(y-methyl D,L-glutamate) have been made by et al 15 and Nakajima et af.1 6 and show that the helical content in the membranes steadily decreases from 100% to 80% as the fraction of the Dresidue is increased from 0 to 50%. Furthermore, these authors found that the helical content of the right-handed a-helical form for poly(y-methyl D,Lglutamate) in which D-residue is 50% equals the helical content of the left-handed form.…”
mentioning
confidence: 99%
“…Poly-a-amino acids have been investigated for various biomedical materials, such as hemodialysis membranes and synthetic vascular prostheses. 2 -4 Block copolymers containing poly-a-amino acid as one component should be excellent biomedical materials, since it has been reported by Lyman et al, S Nyilas et a/., 6 and Okano et al 7 that the microheterophase structure characteristic of the block copolymers plays an important role in blood compatibility. In fact, biomembranes have a microhet-erophase structure composed of both hydrophilic and lipophilic domains.…”
mentioning
confidence: 99%
“…Values were obtained using the graphical method o f Fowkes (30) ancl y ,~ \values from tlie literature (31). For the control 1' I:OMA films, Y ,~, was very close to the y, value, indicating n o polar contril~ution.…”
Section: -mentioning
confidence: 99%